Physical, chemical and morphological properties of laterite soil in Bandar Baharu District - Ros Nadiah Rosli,; Aizat Mohd Taib,; Siti Aimi Nadia Mohd Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Bandar Baharu District in southern of Kedah, Malaysia is extremely rich in laterite soil. The district is distinguished by the widespread presence of laterite soil, making it critical to thoroughly explore its physical, chemical, and morphological properties. Understanding these properties is essential for determining the acceptability and behaviour of laterite soil in a variety of engineering and building applications. Thus, the objective of this study is to analyze and evaluate the physical, chemical, and morphological properties of the selected laterite soil. Three sources of laterite soils have been identified in Sungai Kechil, Bandar Baharu, and Relau. The samples are labeled as SS-A, SS-B, and SS-C. The soils are categorized as SM, SC and MH respectively according to classification by Unified Soil Classification System (USCS). Since the pH values were less than 6, all of the soils were acidic. The X-ray fluorescence (XRF) characterization shows that the three soil samples have three main chemical components, namely silicon dioxide (SiO2), aluminium oxide (Al2O3) and iron oxide (Fe2O3). According to the X-Ray diffraction analysis (XRD) results, the minerals discovered in the laterite soils were gibbsite, quartz, kaolinite, and magnetite. Based on the scanning electron microscope (SEM) image, the sample with the highest fine particle content, which is 55.7% for the SS-C sample, shows the smallest pore size